2003
DOI: 10.1034/j.1399-0012.2003.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell function testing: an adjunct to therapeutic drug monitoring in transplant patient management

Abstract: Each year, 55 000 organ transplants are performed worldwide. Cumulatively, the number of living organ recipients is now estimated to be over 300 000. Most of these transplant recipients will remain on immunosuppressive drugs for the remainder of their lives to prevent rejection episodes. Controlled doses of these drugs are required to prevent over-medication, which may leave the patient susceptible to opportunistic infection and drug toxicity effects, or under-dosing, which may lead to shortened graft survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
211
5
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(232 citation statements)
references
References 19 publications
14
211
5
2
Order By: Relevance
“…This assay is marketed commercially as ImmunKnow-the Cylex Immune Cell Function Assay. On the basis of a multicenter study, this assay was approved by the Food and Drug Administration for monitoring cell-mediated immunity in immunosuppressed patients (65). This assay is performed by stimulating whole blood (i.e., lymphocytes in the presence of circulating levels of immunosuppressive drugs) with phytohemagglutinin for 12 to 15 h. CD4 ϩ T cells are isolated by magnetic bead selection.…”
Section: T Cell Responses To Polyclonal Non-antigen-specific Stimulamentioning
confidence: 99%
“…This assay is marketed commercially as ImmunKnow-the Cylex Immune Cell Function Assay. On the basis of a multicenter study, this assay was approved by the Food and Drug Administration for monitoring cell-mediated immunity in immunosuppressed patients (65). This assay is performed by stimulating whole blood (i.e., lymphocytes in the presence of circulating levels of immunosuppressive drugs) with phytohemagglutinin for 12 to 15 h. CD4 ϩ T cells are isolated by magnetic bead selection.…”
Section: T Cell Responses To Polyclonal Non-antigen-specific Stimulamentioning
confidence: 99%
“…ImmuKnow® (Cylex, Columbia, MD) is a novel and promising in vitro assay for measuring the cell function of stimulated T cells. 1 Bhorade et al. 2 reported that ImmuKnow® levels were lower in lung transplant recipients with infection than in non-infected recipients.…”
Section: Introductionmentioning
confidence: 99%
“…The test requires an incubation of whole blood overnight in the presence of the mitogen phytohemagglutinin (PHA) and an isolation of CD4 T-cells with magnetic particles. The ATP is then measured by luminometry [4] . Whole blood anticoagulated with heparin can be stored up to 30 h at room temperature [5] .…”
Section: Biomarkers Of Immune Activation Atp Concentration In Cd4 T-cmentioning
confidence: 99%